2022
DOI: 10.13057/biodiv/d230324
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of mangrove vegetation species, salinity, and mud thickness in mangrove forest in Pangarengan, Cirebon, Indonesia

Abstract: Abstract. Purwanto RH, Mulyana B, Satria RA, Yasin EHE, Putra ISR, Putra AD. 2022. Spatial distribution of mangrove vegetation species, salinity, and mud thickness in mangrove forest in Pangarengan, Cirebon, Indonesia. Biodiversitas 23: 1384-1392. The mangrove rehabilitation programs in the northern coastline of West Java showed varying levels of success due to the lack of information on habitat suitability and species distribution. This research aimed to investigate the spatial distribution of mangrove vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The preference for using R. mucronata to plant mangroves also makes this species more dominant in Muarareja Village (Tegal City). The findings of Purwanto et al (2022) suggest that R. mucronata might be a good choice. Since 1997 to enhance the likelihood of success in mangrove rehabilitation programs, mangroves have been planted in Brebes as a measure intended to prevent further abrasion (Susantoro et al 2020).…”
Section: Species Compositionmentioning
confidence: 98%
“…The preference for using R. mucronata to plant mangroves also makes this species more dominant in Muarareja Village (Tegal City). The findings of Purwanto et al (2022) suggest that R. mucronata might be a good choice. Since 1997 to enhance the likelihood of success in mangrove rehabilitation programs, mangroves have been planted in Brebes as a measure intended to prevent further abrasion (Susantoro et al 2020).…”
Section: Species Compositionmentioning
confidence: 98%
“…Another research was conducted on Indonesian mangroves in Gorontalo (Kasim et al 2019), North Maluku (Serosero et al 2020), East Kalimantan (Edwin et al 2021), and West Lombok (Sukuryadi et al 2021) recorded 9, 10, 15 and 12 species, respectively. However, species composition in Benoa Bay's Rhizophora zone had a higher species number than Mare Island (Akbar et al 2016), Jakarta Bay , Situbondo, East Java (Hariyanto et al 2019), Mantehage-Paniki Islands, North Sulawesi (Opa et al 2019) and Cirebon (Purwanto et al 2022) were only found five true mangrove species. Several mangrove species were co-dominantly identified with Rhizophora, such as A. alba, B. hainesii, B. parviflora, E. agallocha, H. littoralis, L. littorea, S. hydrophyllacea, S. ovata and X. moluccensis, as found in Riau (Prianto et al 2006), and A. officinalis, B. cylindrica, B. sexangula, S. caseolaris in North Sumatra, Indonesia (Harefa et al 2022).…”
Section: Mangrove Community Structurementioning
confidence: 99%
“…The occurrence may arise due to the distinctive attributes of this ecosystem, which serve as inhibitory factors for species. In addition to their high salinity, mangrove forests are also affected by tidal cycles (Froilan et al, 2020;Matatula et al, 2019;Purwanto et al, 2022).…”
Section: Discussionmentioning
confidence: 99%